DESIGNING MARKETING STRATEGY BASED ON VALUE FROM CLOTHING-PRODUCING COMPANIES USING THE AHP AND DELPHI METHODS - Sari, Hasrini; Nurhadi, Diningtyas Aulia (Jurnal Teknik Industri, 2019)
Organizations design some strategies to win the competition. This paper discusses the design of market strategies to achieve harmony between value-based segmentation and marketing mix.  The strategy's implementation starts with segmentation, targeting, and positioning. The clothing company ("M") was selected as a research object. Identification of market segments using cluster analysis while determine the target market using the AHP and Delphi method. Besides, Bull's eye research was used for product positioning. The results show that "M" customers are classified into two groups, referred Big Spenders and Discount Finders. Big Spender selected as the primary target market with a focus on size and durability. The marketing strategy focuses on Instagram and Facebook.  As a result, the ads developed prototypes have proven to be better.